2019
DOI: 10.4274/balkanmedj.galenos.2018.2017.1034
|View full text |Cite
|
Sign up to set email alerts
|

Novel SNARE Complex Polymorphisms Associated with Multiple Sclerosis: Signs of Synaptopathy in Multiple Sclerosis

Abstract: Background: It is well known that axonal degeneration plays a role in disability in patients with multiple sclerosis, and synaptopathy has recently become an important issue. Aims: To investigate the possible roles of selected synaptic and presynaptic membrane protein genetic polymorphisms (VAMP2, SNAP-25, synaptotagmin, and syntaxin 1A) in patients with multiple sclerosis. Study Design: Case-control study. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(46 reference statements)
0
13
1
Order By: Relevance
“…The VAMP2 gene is located on chromosome 17p13.1 and consists of 6 exons that encode for the SNARE complex key protein required for membrane fusion. A VAMP2 gene 26 bp Ins/Del polymorphism, located in a intergenic region, suspected to be involved in gene expression, distant 2 kb from the 3′ flanking region of VAMP2 was associated with neurological disease like Attention-deficit hyperactivity disorder and with neurodegenerative disease like Multiple Sclerosis ( Sánchez-Mora et al, 2013 ; Kenar et al, 2014 ; Yalın et al, 2019 ). Notably, a reduction of VAMP2 expression in the hippocampus and the entorhinal cortex was found to be associated with cognitive decline ( Sze et al, 2000 ) and AD brains have a reduced level of VAMP2, STX1a and SNAP-25 compared to control brains ( Pham et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The VAMP2 gene is located on chromosome 17p13.1 and consists of 6 exons that encode for the SNARE complex key protein required for membrane fusion. A VAMP2 gene 26 bp Ins/Del polymorphism, located in a intergenic region, suspected to be involved in gene expression, distant 2 kb from the 3′ flanking region of VAMP2 was associated with neurological disease like Attention-deficit hyperactivity disorder and with neurodegenerative disease like Multiple Sclerosis ( Sánchez-Mora et al, 2013 ; Kenar et al, 2014 ; Yalın et al, 2019 ). Notably, a reduction of VAMP2 expression in the hippocampus and the entorhinal cortex was found to be associated with cognitive decline ( Sze et al, 2000 ) and AD brains have a reduced level of VAMP2, STX1a and SNAP-25 compared to control brains ( Pham et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the level of PSD95 and SYP proteins related to synapse structure was also measured. SYP is a presynaptic vesicle protein that plays an import role in synaptic vesicle release 23 . The lack of SYP may induce a decrease in synaptic vesicles, which can disturb neurotransmitter release and synaptic network activity 24 .…”
Section: Discussionmentioning
confidence: 99%
“…SYP is a presynaptic vesicle protein that plays an import role in synaptic vesicle release. 23 The lack of SYP may induce a decrease in synaptic vesicles, which can disturb neurotransmitter release and synaptic network activity. 24 It is reported that several synaptic proteins including PSD95 and SYP play an important role in the regulation of the spine formation and synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent studies reported that axonal degeneration may be prominent in the beginning of the inflammation period of MS, as well as being one of the major determinants of permanent neurological impairment. 8,9 Synaptopathy, which is defined as the alteration of the synaptic structure and function, has been associated with various neurological diseases, including epilepsy, autism, Alzheimer's disease, and recently MS. Inflammatory-dependent synaptopathy is of particular interest because it is potentially reversible and may represent a novel therapeutic target for MS. 10 At the presynaptic terminal, the membrane fusion process is primarily mediated by the soluble Nethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex. 11 The SNARE complex is mainly composed of three proteins: VAMP-2, syntaxin-1, and SNAP-25.…”
Section: Introductionmentioning
confidence: 99%